Comparison of the Mean DMF Index in Type I Diabetic and Healthy Children - Sahba Kamran; Hamid Moradian; Elnaz Yazdan Bakhsh (Shiraz University of Medical Sciences, 2019)
Statement of the Problem: It is expected that the prevalence of caries would be more in diabetics than in non-diabetic individuals due to the complications subsequent to metabolic changes such as xerostomia and increased glucose level in saliva. On the other hand, the restriction of glucose consumption in the diabetics' diet would be a reason to justify decreasing dental caries in them. Purpose: The aim of this study was to compare the mean DMF (decayed, missed due to decay, and filled teeth) index in type I diabetic and healthy children. Materials and Method: The DMF index was assessed in 100 type I diabetic children (9-14 years-old, mean= 12±1.23) and compared with the DMF index in 100 age- and sex-matched metabolically healthy controls. Data were collected through a questionnaire and clinical examinations and analyzed statistically by t-test and one-way ANOVA. Results: The results showed that there were no significant differences between the mean DMF index of diabetic children and healthy children. The mean DMF was significantly lower in those who regularly used a toothbrush and dental floss than in those who did not use in both groups (p< 0.05). Conclusion: Diabetes did not affect dental condition by itself but adequate oral hygiene had an important role in controlling caries and promoting oral status.